Tinjauan Yuridis Terhadap Kesiapan Kewajiban Spin Off Bagi UnitUsaha Syariah (UUS) Menjadi Bank Umum Syariah (BUS) - Wiwin Muchtar Wiyono; Iskatrinah (Wijayakusuma Law Review, 2022)
Law Number 21 of 2008 concerning Sharia Banking in Article 68 paragraph 1 and Article 40 Article 40 PBI No.11/10/ PBI / 2009 mandates that every Sharia Business Unit (UUS) that becomes a sharia unit at aConventional Commercial Bank (BUK) to separate itself (spin-off). and explained that UUS is required toseparate into BUS if UUS asset value has reached 50% (fifty percent) of the total asset value of its parent BUK.The spin-off time is no later than 15 (fifteen) years since the law was enacted, namely in 2023. If the spin-offorder is not carried out by each UUS, then Bank Indonesia as the central bank will impose sanctions in the formof revocation of operational licenses. But the problem that arises is in the face of time spin-offs are not a fewUUS are overwhelmed in preparing capital so that they have not been able to stand on their own afterseparating. The purpose of writing is to find out the impact of the spin-off for UUS by analyzing the solutionsthat can be offered. The results of the study indicate that it is necessary to review Law Number 21 of 2008concerning Islamic Banking by considering the financial condition of UUS. In addition, UUS which have carriedout a spin-off by becoming a new BUS can optimize the utilization of Third Party Funds in the form of financingand other services. In order to encourage the growth of BUS, support from the government is needed, such asproviding tax incentives and simplifying regulations on equity participation. In addition, the new BUS needs tocarry out various innovations by adding financing products and developing products that have beenimplemented. This study aims to provide an overview of the readiness of the Spin Off obligations for UUS tobecome BUS and issues related to readiness to fulfill UUS obligations to become BUS in July 2023.